2008
DOI: 10.1152/ajpgi.90356.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia stimulates pancreatic stellate cells to induce fibrosis and angiogenesis in pancreatic cancer

Abstract: Pancreatic cancer is characterized by excessive desmoplastic reaction and by a hypoxic microenvironment within the solid tumor mass. Chronic pancreatitis is also characterized by fibrosis and hypoxia. Fibroblasts in the area of fibrosis in these pathological settings are now recognized as activated pancreatic stellate cells (PSCs). Recent studies have suggested that a hypoxic environment concomitantly exists not only in pancreatic cancer cells but also in surrounding PSCs. This study aimed to clarify whether h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
158
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(170 citation statements)
references
References 37 publications
(60 reference statements)
6
158
0
Order By: Relevance
“…Severe intratumoural hypoxia is present in pancreatic cancer 25, 37, suggesting that hypoxia plays a role in the accumulation and activation of β‐catenin in pancreatic cancer cells. As a Wnt antagonists, it is reported that DKK3 overexpression does not affect nuclear/cytoplasmic accumulation of β‐catenin 11.…”
Section: Discussionmentioning
confidence: 99%
“…Severe intratumoural hypoxia is present in pancreatic cancer 25, 37, suggesting that hypoxia plays a role in the accumulation and activation of β‐catenin in pancreatic cancer cells. As a Wnt antagonists, it is reported that DKK3 overexpression does not affect nuclear/cytoplasmic accumulation of β‐catenin 11.…”
Section: Discussionmentioning
confidence: 99%
“…Many genes involved in tumor biology are regulated by levels of oxygen. In some human tumor types, hypoxia inducible factor-1α (HIF-1α) is overexpressed compared with corresponding normal tissues (Zhong et al, 1999;Furlan et al, 2007;Fan et al, 2008;Hamaguchi et al, 2008;Liang et al, 2008;Masamune et al, 2008;Sayed et al, 2008;Simiantonaki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The major non-malignant cellular components of the tumour microenvironment, the pancreatic stellate cells and tumour-associated macrophages, have been suggested to be involved in the progression of pancreatic cancer by creating a favourable tumour microenvironment and stimulate invasion, tumour growth, and development of metastases (Hwang et al, 2008, Masamune et al, 2008, Neyen et al, 2013, Green et al, 2009 TPSCs such as uPA, FGF and PDGF may likely also be involved (Rosendahl et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that the pancreatic stellate cells, myofibroblast-like cells in the pancreatic microenvironment, are responsible for this stromal reaction due to their ability to produce large quantities of ECM and influence the composition and turnover of ECM proteins (Yen et al, 2002, Erkan et al, 2009, Apte et al, 2004. In addition, they may promote the pathogenesis of pancreatic cancer by creating a favourable tumour microenvironment through secretion of growth-and angiogenic factors as well as stimulating cancer cell migration (Tod et al, 2013, Hwang et al, 2008, Masamune et al, 2008. Although pancreatic stellate cells have an established role in the desmoplastic stroma, further investigations are needed to elucidate the influence by paracrine communication and cell-cell interactions with the tumour microenvironment on invasive properties of the cancer cells.…”
Section: Introductionmentioning
confidence: 99%